Morphological and molecular characterization of Penicillium rubens sp.nov isolated from poultry feed - Sawant, Amol M.; Vankudoth, Ramu; Navale, Vishwambar; Kumavat, Rajkamal; Kumari, Prabla; Santhakumari, B.; Vamkudoth, Koteswara Rao (Indian Phytopathology, 2019)
Fungi are the second largest group of eukaryotic organisms, estimates ranging from 2.2 to 3.8 million and 120,000 currently accepted species. Unfortunately, identification of Penicillium species is an overwhelming task even for taxonomic experts. In the current study, we isolated identified and morphologically characterized Penicillium rubens strain NCIM-1397. Molecular characterization of P. rubens by multilocus sequence analysis (MLSA) of internal transcribed spacer (ITS) region, β-tubulin (BenA), calmodulin (CaM), NL (D1/D2 region) and LR (large subunit region) gene. Conversely, BenA gene differentiated P. rubens from P. chrysogenum. Moreover, Vitek MS, Matrix-assisted laser desorption ionization–time of flight mass spectrometer (MALDI-TOF–MS) failed to discriminate to strain level. Metabolic profiling of P. rubens enable to produce roquefortine C, chrysogine, meleagrine, sorbicillin and non-producers for industrially important metabolite, penicillin determined by LC–MS. Even, In addition, even molecular detection of penicillin biosynthetic pathway genes, PcbC, PenDE and Phl were negative by PCR. Nevertheless, P. rubens showed 90–100% toxicity/pathogenicity on seed germination of sorghum (Sorghum bicolor) and no further development of coleoptiles, radicle and leaf length observed. Also, it showed non-toxic to animal cell determined on Human foreskin fibroblast (HFF) cell line by In-Vitro.